2019
DOI: 10.4103/psychiatry.indianjpsychiatry_285_17
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between dysfunctional beliefs and stress coping methods in drug-addicted patients: A sample of Turkey

Abstract: Background:Dysfunctional beliefs are believed to have an effect on substance abuse. Drug-addicted individuals experience difficulties with coping in stressful situations and therefore, start reusing these drugs.Aim:This study was conducted to determine the relationship between dysfunctional beliefs and stress coping methods in drug-addicted patients.Materials and Methods:The population of this descriptive and cross-sectional research study comprised 51 patients who were admitted to the Alcohol and Drug Addicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Moreover addictive persons were also found with dysfunctional attitudes [20]. Another study also explored that drug abuser had dysfunctional thinking opinions and display emotional-based coping approaches [21].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover addictive persons were also found with dysfunctional attitudes [20]. Another study also explored that drug abuser had dysfunctional thinking opinions and display emotional-based coping approaches [21].…”
Section: Resultsmentioning
confidence: 99%
“…Also, a study done by Yigitoglu and Keskin concluded that substance abusers have dysfunctional beliefs and exhibit emotion-focused coping attitudes. They theoretically reasoned those dysfunctional beliefs could generate maladaptive coping attitudes, and they may result from substance abuse behavior (39).…”
Section: Discussionmentioning
confidence: 99%
“…Since dysfunctional coping behavior is associated with both substance and behavioral addictions, it is not surprising that there is an association between dysfunctional coping and problematic Internet use. (e.g., Yiğitoğlu & Keskin, 2019). Griffiths (2005) states that any individual who engages in a behavior that meets the six aforementioned criteria (i.e., mood modification, salience, tolerance, withdrawal, conflict, and relapse) should be operationally defined as addicted to that behavior.…”
Section: Problematic Internet Usementioning
confidence: 99%